Prognostic and clinicopathological value of Beclin-1 expression in hepatocellular carcinoma: a meta-analysis - Zhiqiang Qin; Xinjuan Yu; Mei Lin; Jinkun Wu; Shupei Ma; Ning Wang (World Journal of Surgical Oncology, 2018)
Abstract Background The abnormal expression of Beclin-1 has recently been investigated in a variety of tumors. However, previous studies have obtained contradicting results regarding the clinical and prognostic value of Beclin-1 in hepatocellular carcinoma (HCC). We performed a meta-analysis to clarify the prognostic value of Beclin-1 and its correlations with clinical pathological parameters in HCC. Methods Relevant studies were systematically retrieved from PubMed, EMBASE, China National Knowledge Infrastructure (CNKI), Wan Fang and Chinese VIP databases. We used the Newcastle-Ottawa scale (NOS) to estimate the quality of the involved studies. Results Ten eligible studies with 1086 HCC patients were included in this study. Our results showed that decreased Beclin-1 expression in HCC related to histological grade [poor-undifferentiated vs. well-moderate: odds ratio (OR) = 2.34, 95% confidence interval (CI) = 1.65–3.32, P < 0.00001]. The pooled hazard ratio (HR) (HR = 1.43, 95% CI = 1.17–1.75, P = 0.0004) indicated that decreased Beclin-1 expression correlated with poor overall survival (OS). Conclusions This meta-analysis indicated that decreased Beclin-1 expression might relate to poor differentiation and unfavorable outcome in HCC.